Acral Acanthosis Nigricans in a Case of Scleroderma - Kura, Mahendra M (Indian J Dermatol, 2015)
Acanthosis nigricans (AN) is a dermatosis characterized by velvety, papillomatous, brownish-black, hyperkeratotic plaques, typically on the intertriginous surfaces and neck. The majority (80%) of AN occurs idiopathically or in benign conditions such as endocrinopathies like diabetes mellitus, polycystic ovary syndrome; metabolic syndrome and/or heritable disease. Malignancy-associated AN is rare. AN may rarely be associated with autoimmune diseases including systemic lupus erythematosus, due to antibodies to the insulin receptor, so-called type B insulin resistance. Here we report a case of AN in a case of diffuse progressive systemic sclerosis without evidence of insulin resistance.